Investigating Pulsed Discharge Polarity Employing Solid-state Pulsed Power Electronics - Davari, P.; Zare, Firuz; Blaabjerg, F. (Taylor & Francis, 2015)
© 2015 Taylor & Francis Group, LLC. The power electronics technique has become a key technology in solid-state pulsed power supplies. Since pulsed power applications have been matured and found their way into many industrial applications, moving toward energy efficiency is gaining much more interest. Therefore, finding an optimum operation condition plays an important role in maintaining the desired performance. Investigating the system parameters contributed to the generated pulses is an effective way in improving the system performance further ahead. One of these parameters is discharge polarity, which has received less attention. In this article, the effects of applied voltage polarity on plasma discharge have been investigated in different mediums at atmospheric pressure. The experiments have been conducted based on a high-voltage DC power supply and a high-voltage pulse generator for point-to-point and point-to-plane geometries. Furthermore, the influence of electric field distribution is analyzed using finite-element simulations for the employed geometries and mediums. The experimental and simulation results have verified the important role of the applied voltage polarity, employed geometry, and medium of the system on plasma generation.